Orações concessivas independentes à luz da gramática discursivo-funcional - Garcia, Talita Storti [UNESP]; Pezatti, Erotilde Goreti [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This paper investigates, in light of the theory of Functional Discourse Grammar (HENGEVELD; MACKENZIE, 2008), the concessive clause that is not subordinated to other clauses, i.e., it has no semantic or syntactic relations with clauses before or after it, and which we call Independent Concessive. The aim is to describe the discursive properties and the semantic, morphosyntactic and prosodic structure of this type of clause, showing that its relevance is in the construction and organization of discourse. The results indicate that the Independent Concessive works in speech as a parenthesis which interrupts the discursive course and is then highlighted by a special prosodic contour, combined with the presence of Interactive Acts. It is therefore a Move, the highest layer of the Interpersonal Level, the level that relates to the pragmatic aspects of the grammar of a language. The universe of research used is the Iboruna corpus, a database that records a variety of Portuguese from the Northwest of São Paulo.

Este artigo investiga, à luz da Teoria da Gramática Discursivo-Funcional (HENGEVELD; MACKENZIE, 2008), a oração concessiva que não é subordinada a outras orações, ou seja, não apresenta relações sintáticas nem semânticas com orações anteriores ou posteriores, a que denominamos Concessiva Independente. O objetivo deste estudo consiste em descrever as propriedades discursivas, semânticas, morfossintáticas e prosódicas desse tipo de estrutura, mostrando que sua relevância está na construção e organização do discurso. Os resultados apontam que a Concessiva Independente funciona, no discurso, como um parêntese, que interrompe o fio discursivo, sendo, então, destacado por um contorno prosódico especial, aliado à presença de Atos Interativos. Constitui, portanto, um Movimento, a camada mais alta do Nível Interpessoal, nível que se relaciona aos aspectos pragmáticos da gramática de uma língua. O universo de investigação utilizado é o córpus Iboruna, um banco de dados que registra a variedade do português do noroeste paulista.
Independent concessive clauses in the light of functional discourse grammar
Keywords: Oração adverbial concessiva; Orações concessivas independentes; Teoria da Gramática Discursivo-Funcional; Movimento; Nível interpessoal; Concessive adverbial clause; Independent concessive clause; Functional Discourse Grammar Theory; Moves; Interpersonal level